2019
DOI: 10.1038/s41467-019-08300-3
|View full text |Cite
|
Sign up to set email alerts
|

The lineage stability and suppressive program of regulatory T cells require protein O-GlcNAcylation

Abstract: Regulatory T (Treg) cells control self-tolerance, inflammatory responses and tissue homeostasis. In mature Treg cells, continued expression of FOXP3 maintains lineage identity, while T cell receptor (TCR) signaling and interleukin-2 (IL-2)/STAT5 activation support the suppressive effector function of Treg cells, but how these regulators synergize to control Treg cell homeostasis and function remains unclear. Here we show that TCR-activated posttranslational modification by O-linked N-Acetylglucosamine (O-GlcNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
96
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(97 citation statements)
references
References 66 publications
0
96
1
Order By: Relevance
“…Recent studies indicated that O-GlcNAcylation is implicated in both differentiation and homeostasis of Th17 and Treg cells (Fig. 2d, lower right panel) [140][141][142]. Administration of Thiamet-G increased the binding of RORγt, a pivotal transcription factor for commitment of the Th17 lineage [143], to Il-17 promoter and therefore promotes IL-17 production and Th17 differentiation.…”
Section: Role Of O-glcnacylation In T Cellsmentioning
confidence: 91%
See 1 more Smart Citation
“…Recent studies indicated that O-GlcNAcylation is implicated in both differentiation and homeostasis of Th17 and Treg cells (Fig. 2d, lower right panel) [140][141][142]. Administration of Thiamet-G increased the binding of RORγt, a pivotal transcription factor for commitment of the Th17 lineage [143], to Il-17 promoter and therefore promotes IL-17 production and Th17 differentiation.…”
Section: Role Of O-glcnacylation In T Cellsmentioning
confidence: 91%
“…It has been reported that FOXP3 is stabilized by O-GlcNAcylation, and that O-GlcNAcylation is required for IL-2/STAT5 signalingmediated FOXP3 expression. Depletion of Ogt in Treg cells in mice dramatically reduced Treg lineage stability, which resulted in a severe autoimmune phenotype [141]. Thus, O-GlcNAcylation is required for the maintenance of lineage stability and regulatory function of Treg cells.…”
Section: Role Of O-glcnacylation In T Cellsmentioning
confidence: 99%
“…The immunosuppressive features of tumor lesions participate not only as one of the major players inducing cancer progression but also a big challenge for effective immunotherapy. It has been found that immunosuppression associated with chronic inflammatory factors, such as growth factors, cytokines, and chemokines is generated by stroma and tumor cells [14,15]. Multiple immune cells coexist and interact in a complex series of pathways that ultimately lead to tumor carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies highlight the immunosuppressive functions of TME in favoring the HCC progression and potential drug resistance. The initiation of such immune-tolerant microenvironment is mediated by numerous inflammatory factors such as growth factors, cytokines, chemokines generated by multiple cell types co-existed and interacted in TME [ 92 , 93 ]. Of them, the key constructive cells include TAMs, marrow-derived suppressor cells (MDSCs), tumor-associated neutrophils, CAFs, as well as infiltrating T cells and natural killer (NK) cells [ 94 ].…”
Section: Cafs In Hccmentioning
confidence: 99%